Identification of Genetic Predisposition in Noncirrhotic Portal Hypertension Patients With Multiple Renal Cysts by Integrated Analysis of Whole-Genome and Single-Cell RNA Sequencing - Wu, Yanjing; Wu, Yongle; Liu, Kun; Liu, Hui; Wang, Shanshan; Huang, Jian; Ding, Huiguo (Frontiers in Genetics, 2021)
BACKGROUND & AIMS: The multiple renal cysts (MRC) occur in some patients with noncirrhotic portal hypertension (NCPH) could be a subset of ciliopathy. However, the potential genetic influencers and/or determinants in NCPH with MRC are largely unknown. The aim of this study was to explore the potential candidate variants/genes associated with those patients. METHODS: 8295 cirrhotic patients with portal hypertension were enrolled in cohort 1 and 267 patients affected with NCPH were included in cohort 2. MRC was defined as at least two cysts in both kidneys within a patient detected by ultrasonography or computed tomography. Whole-genome sequencing (WGS) was performed in nine patients (four from cohort 1 and five from cohort 2). Then we integrated WGS and publicly available single-cell RNA sequencing (scRNA-seq) was conducted to prioritize potential candidate genes. Genes co-expressed with known pathogenic genes within same cell types were likely associated NCPH with MRC. RESULTS: The prevalence of MRC in NCPH patients (19.5% ,52/267) was significantly higher than cirrhotic patients (6.2%, 513/8295). Further, the clinical characteristics of NCPH patients with MRC were distinguishable from cirrhotic patients, including late-onset, more prominent portal hypertension however having preserved liver functions. In the nine whole genome sequenced patients, we identified 3 patients with early onset harboring compound rare putative pathogenic variants in the known disease gene PKHD1. For the remaining patients, by assessing cilia genes profile in kidney and liver scRNA-seq data, we identified CRB3 was the most co-expressed gene with PKHD1 that highly expressed in ureteric bud cell, kidney stromal cell and hepatoblasts. Moreover, we found a homozygous variant，CRB3p.P114L, that caused conformational changes in the evolutional conserved domain, which may associate with NCPH with MRC. CONCLUSIONS: scRNA-seq enables unravelling cell heterogeneity with cell specific gene expression across multiple tissues. With the boosting public accessible scRNA-seq data, we believe our proposed analytical strategy would effectively help disease risk gene identification.